Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2022
DOI: 10.3389/fendo.2021.825336
|View full text |Cite
|
Sign up to set email alerts
|

Association Between Pre-Pregnancy Body Mass Index and Maternal and Neonatal Outcomes of Singleton Pregnancies After Assisted Reproductive Technology

Abstract: ObjectiveTo study the association between pre-pregnancy body mass index (BMI) and adverse maternal and neonatal outcomes of singleton pregnancies after assisted reproductive technology (ART).MethodsThis hospital-based retrospective cohort study of women with live singleton births through ART in China from January 2015 to August 2020 included 3043 Chinese women. According to the latest BMI classification standard of Asian women, the women included in this study were classified as underweight (BMI <18.5 k… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(9 citation statements)
references
References 39 publications
0
6
0
Order By: Relevance
“…The authors concluded that women with overweight or obesity who had ART for a singleton pregnancy were significantly more likely to have a cesarean section, gestational diabetes mellitus, gestational hypertension, and preeclampsia. Furthermore, neonates born to mothers with obesity were more likely to have macrosomia [ 15 ]. Despite querying different population, the findings of Sun et al are generally in line with those of the present analysis.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The authors concluded that women with overweight or obesity who had ART for a singleton pregnancy were significantly more likely to have a cesarean section, gestational diabetes mellitus, gestational hypertension, and preeclampsia. Furthermore, neonates born to mothers with obesity were more likely to have macrosomia [ 15 ]. Despite querying different population, the findings of Sun et al are generally in line with those of the present analysis.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, recent studies suggested that women with obesity who had ART for a singleton pregnancy were more likely to have a cesarean section, gestational diabetes mellitus, gestational hypertension, and preeclampsia [ 15 , 16 ]. However, the evidence on the clinical impact of high BMI on various maternal and child-health outcomes in women receiving ART is not sufficient and remains to be clarified, particularly in a nationwide cohort.…”
Section: Introductionmentioning
confidence: 99%
“…Various studies have reported similar findings, so Jagan et al in 2020 (Jagan, et al, 2020) and Doherty et al, in 2006 (Doherty, et al, 2006) reported an increased risk of both gestational hypertension and pre-eclampsia in the control group and obese group). Maternal age as a factor risk factor for pregnancy outcomes, such as gestational diabetes mellitus, preeclampsia, and premature delivery is shown in previous studies (Sun, et al, 2022;Wei, et al, 2015;Vinturache, et al, 2014). Despite that, Claramonte et al, in their study reported that maternal age was associated with a high risk of cesarean section, and gestational diabetes (Claramonte, et al, 2019).…”
Section: Discussionmentioning
confidence: 92%
“…[4,5] Although the conclusions of various studies are different, multiple studies have shown that overweight/obesity has an adverse effect on IVF pregnancy outcomes and increases maternal and fetal complications. [6,7] To evaluate the final outcome of a patient assisted fertility cycle, it is necessary to consider both the fresh transfer cycle and the subsequent frozen-thawed embryo transfer (ET) cycle. The cumulative live birth rate (CLBR), as an evaluation indicator for a complete oocyte retrieval cycle, has more practical significance for patients than the previous clinical pregnancy rate and delivery rate.…”
Section: Introductionmentioning
confidence: 99%
“…[4,5] Although the conclusions of various studies are different, multiple studies have shown that overweight/obesity has an adverse effect on IVF pregnancy outcomes and increases maternal and fetal complications. [6,7]…”
Section: Introductionmentioning
confidence: 99%